Comments on the design of trellis coded MPSK for fading channels: Set partitioning for optimum code design - Rajab, Hassan Abou (Institute of Electrical and Electronics Engineers Inc., 2006)
Multiple trellis coded modulation (MTCM) which assigns more than one signal per trellis branch achieves better signal diversity than conventional TCM for the transmission of digital information on a fading channel. The paper above presents a set partitioning method which was claimed to maximize the effective length (Lmin) and the minimum product distance (dpmin). In this paper, it is observed that this set partitioning did not take into account that the MPSK signal sets (M>4) are nonregular where then the worst case distance corresponding to each signal selector should be considered. © 2006 IEEE.
2nd International Conference on Information and Communication Technologies: From Theory to Applications, ICTTA 2006 -- 2006-04-24 through 2006-04-28 -- Damascus -- 117880
Keywords: Trellis codes; Code designs; Digital information; Multiple-trellis coded modulations; Product distance; Set partitioning; Set partitioning method; Signal diversity; Signal set; Fading channels